Human relationships the key to social and emotional development - Shapiro, Leah; Spielberger, Spiel; Magna Systems, Inc. (Lake Zurich, Ill. : Magna Systems Inc., 2005)
supervisors discuss the characteristics of an effective group worker for school-age children. This video demonstrates the conflict resolution skills utilized by experienced group workers and the techniques thy use in working with the nine to twlve year-old youth
Title from title screen
Module 3
School age care
Camera/editor, Nick Kolias ; educational consultants, Leah Shapiro, Julie Spielberger
Narrator: Sheron shapiro
Keywords: Interpersonal relations; Social interaction; Social psychology; School-age child care